Diversifikasi Produk Hasil Fermentasi Ikan Pedo menjadi Ikan Pedo Siap Konsumsi pada UMKM di Desa Biaro Kabupaten Musi Rawas Utara - Metha Aditya Putri; Susyanto Tunut; Fatma Oktarendah (IPM2KPE, 2024)
This research applies a diversification approach or development of fermented fish products with the aim of maintaining business stability, increasing profits, taking advantage of existing market trends, and increasing resource efficiency. The research method used is qualitative descriptive data analysis. It is hoped that the results of this research can increase sales of fermented pedo fish products, as well as develop Micro, Small and Medium Enterprises (MSMEs) in Biaro Village, North Musirawas Regency. The product resulting from this research is ready-to-consume pedo fish with practical packaging, making it easier for people to consume it. Apart from that, the fermented pedo fish production can also be vacuumed, turning it into a frozen food product. In conclusion, it is hoped that it can make a positive contribution to the development of local MSMEs, create innovative products that can meet community needs, and maintain local wisdom in food processing. Keywords: Fermentation, Packaging, Development, Products